Termacolores: a wellness tourism project encompassing the wealth of indigenous knowledge - Sandra Velásquez Puerta (Via@)
Traditional knowledge is a differential factor for tourism wellness projects. Tourism dynamics change if an indigenous community values tradition above economic income. The Puracé indigenous reservation in Cauca, Colombia, requested research on traditional knowledge as part of the Termacolores hot spring project. This paper emphasises the interplay with Puracé locals through the participatory action research (PAR) method. The bibliographic review, workshops, and talks highlighted key factors for Termacolores, besides natural places or health benefits of hot springs, such as locals’ familiarity with cultural traditions, local food or plants, as well as bonds between young and older generations. Results of the research include an intangible heritage inventory, multimedia content and the creation of the Traditional Knowledge Custodians group.